Exercise Strategies to Optimize Glycemic Control in Type 2 Diabetes: A Continuing Glucose Monitoring Perspective - van Dijk, Jan-Willem (Diabetes Spectr, 2015)
IN BRIEF The introduction of continuous glucose monitoring (CGM) several years ago enabled researchers to investigate the impact of exercise strategies on 24-hour glycemic control. Such unique information on the glucoregulatory properties of exercise will ultimately lead to more effective exercise programs to prevent and treat type 2 diabetes. This article reviews the role of exercise and physical activity in the treatment of type 2 diabetes, complemented by recent data obtained by CGM.